Analisis Margin Pemasaran dan Farmer's Share Kopi Arabika Sumatera Utara Tahun 2024 - Lokot Muda Harahap; Raissa Nazswa Indira; Ketrin Hivisini Simbolon; Bintang Emeli Siahaan; Dita Agustina Bintang; Indry Amalia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Price disparities between producers and consumers remain a persistent issue in the marketing of Arabica coffee in North Sumatra, indicating potential inefficiencies in the distribution system. Previous studies have largely focused on micro-level or primary data, while comprehensive analysis using aggregated regional data is still limited. This study aims to analyze marketing margin, farmer’s share, and the level of marketing efficiency of Arabica coffee in North Sumatra in 2024. A quantitative descriptive approach was employed using secondary monthly price data obtained from the Ministry of Agriculture’s Coffee Outlook 2024, covering producer and consumer prices from January to December. The results show that the average marketing margin reached IDR 22,684/kg, while the farmer’s share was 61.78%. Although the farmer’s share indicates that farmers receive a relatively favorable proportion of the final price, the high marketing margin suggests inefficiencies within the distribution chain, likely due to the involvement of multiple intermediaries and limited market access. These findings imply that improving market integration and shortening distribution channels are essential to enhance marketing efficiency and ensure a more equitable distribution of value for coffee farmers.